Obraz czarownicy we współczesnych tekstach kultury (na wybranych przykładach) - Galik, Justyna (Słowo. Studia językoznawcze, 2015)
The aim of the article is to present the picture of the witch in contemporary culture’s texts (a literature, a movie and TV serials). The author shows the image of the witch in specific categories: names of witches, age and origin, place of residence, appearance, paranormal talents, attributes and evaluation. She comes to conclusions that present characters of witches have been very individualized, they differ from one another significantly in terms of nature, appearance and age. Contemporary witches break down prevalent stereotypes.